2011
DOI: 10.1074/jbc.m111.274217
|View full text |Cite
|
Sign up to set email alerts
|

A Sialylated Glycan Microarray Reveals Novel Interactions of Modified Sialic Acids with Proteins and Viruses

Abstract: Many glycan-binding proteins in animals and pathogens recognize sialic acid or its modified forms, but their molecular recognition is poorly understood. Here we describe studies on sialic acid recognition using a novel sialylated glycan microarray containing modified sialic acids presented on different glycan backbones. Glycans terminating in ␤-linked galactose at the nonreducing end and with an alkylamine-containing fluorophore at the reducing end were sialylated by a one-pot three-enzyme system to generate ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
115
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 48 publications
5
115
0
2
Order By: Relevance
“…353 (Kdna2-6Galb1-4GlcNAc) and 256 [Neu5Aca2-6Galb1-4(6OSO3) GlcNAc] are the highest ranking glycans; this suggests the possibility that SNA might prefer sulfated glycans or other sialic acid derivatives, but these motifs do not arise from analysis by GLYMMR, since they are represented fewer than four times on the array. Interestingly, in other work on arrays comprised of derivatives of sialic acid, we observed that SNA preferred Kdn and its acetylated derivatives to Neu5Ac and Neu5Gc, the more common mammalian sialic acids (Song et al, 2011). These results also illustrate the need in glycan microarray studies for presenting glycan determinants in a variety of formats and backbones on multiple glycans to facilitate identification of motifs.…”
Section: Discussionsupporting
confidence: 66%
“…353 (Kdna2-6Galb1-4GlcNAc) and 256 [Neu5Aca2-6Galb1-4(6OSO3) GlcNAc] are the highest ranking glycans; this suggests the possibility that SNA might prefer sulfated glycans or other sialic acid derivatives, but these motifs do not arise from analysis by GLYMMR, since they are represented fewer than four times on the array. Interestingly, in other work on arrays comprised of derivatives of sialic acid, we observed that SNA preferred Kdn and its acetylated derivatives to Neu5Ac and Neu5Gc, the more common mammalian sialic acids (Song et al, 2011). These results also illustrate the need in glycan microarray studies for presenting glycan determinants in a variety of formats and backbones on multiple glycans to facilitate identification of motifs.…”
Section: Discussionsupporting
confidence: 66%
“…5). These fluorescent intensities contain both Neu5Ac and Neu5Gc as terminal sialic acids because of recognition of both Neu5Ac and Neu5Gc by the lectins SNA and MAL-I (27). However, MAL-I cannot detect SA␣2,3Gal linkage of O-glycan, which is recognized by MAL-II (28).…”
Section: Resultsmentioning
confidence: 99%
“…(iv) The difference is derived from reactivities of SNA and MAL-I. According to supplemental material of Song et al (27), SNA bound to Neu5Gc-and Neu5Ac-␣2,6Gal␤1, 4GlcNAc␤1,2Man␣1,3(Neu5Gc-and Neu5Ac-␣2,6Gal␤1, 4GlcNAc␤1,2Man␣1,6)Man␤1,4GlcNAc␤1,4GlcNAcitol (with binding signals being 26,327 and 22,218, respectively, for 10 g/mlSNA)andtoNeu5Gc-andNeu5Ac-␣2,6Gal␤1,4GlcNAc␤1, 3Gal␤1,4Glcitol (with binding signals being 8,544 and 9,187, respectively, for 10 g/ml SNA) but not to Neu5Gc-and Neu5Ac-␣2,6Gal␤1,3GlcNAc␤1,3Gal␤1,4Glcitol (with binding signals being 56 and 96, respectively, for 10 g/ml SNA). Similar structures containing Neu5Gc or Neu5Ac are suggested to be recognized equivalently by SNA.…”
Section: Discussionmentioning
confidence: 99%
“…Although most influenza virus receptor binding research has focused on Neu5Ac and Neu5Gc glycans, sialic acid on cells is expressed with a highly diverse group of modifications (7). In an effort to address the stereochemical nature of potential receptor species for our viruses, we utilized a recently developed glycan microarray that contains chemically derived sialic acid species (65). This array presents 77 sialic acid glycans with 16 different sialic acid modifications in ␣2,3 and ␣2,6 linkages to 3 different precursor glycans.…”
Section: Resultsmentioning
confidence: 99%
“…Both glycans are present on the current CFG array, but a plethora of sialic acid modifications exist in nature which are not found on the current CFG array (72). Therefore, we examined binding of the pseudorevertant viruses to a recently generated modified sialic acid glycan microarray (65). The rH3N1 WT, Y98F/S145I, and Y98F/K238N viruses all bound to sialic acid derivatives, albeit very poorly to some.…”
Section: Discussionmentioning
confidence: 99%